Effect of C-terminal and N-terminal dimerization and alanine scanning on antibacterial activity of the analogs of the peptide p-BthTX-I - Santos-Filho, Norival Alves [UNESP]; Righetto, Gabriela Marinho; Pereira, Marina Rodrigues [UNESP]; Piccoli, Julia Pinto [UNESP]; Almeida, Larissa Mathias Teizen [UNESP]; Leal, Thainá Cristina [UNESP]; Camargo, Ilana Lopes Baratella Cunha; Cilli, Eduardo Maffud [UNESP] (Wiley, 2022)
The peptide (p-BthTX-I)2 [(KKYRYHLKPFCKK)2] and its analog des-Lys12,Lys13-(p-BthTX-I)2 [(KKYRYHLKPFC)2] showed activity against bacteria and potential specificity against prokaryotic cells. In this study, we synthesized the peptide des-Cys11,Lys12,Lys13-(p-BthTX-I)2K [(KKYRYHLKPF)2K] with a Lys instead of a Cys residue in the dimerization step, beginning the SPPS with Fmoc-Lys(Fmoc)-OH. This change avoided Cys oxidation, decreasing one step in the original peptide synthesis and obtaining a smaller and more stable peptide. The antimicrobial activity of the peptide des-Cys11,Lys12,Lys13-(p-BthTX-I)2K was superior to that of the (p-BthTX-I)2 peptide against the bacterial strains tested. Additionally, to evaluate the impact of the linker position on peptide dimerization, we synthesized peptide E(p-BthTX-I)2 [E(KKYRYHLKPFCKK)2] using Fmoc-Glu-OH at the end of the synthesis. This N-terminal dimeric peptide did not increase the antibacterial activity, indicating that the free N-terminal is essential for (p-BthTX-I)2 activity. Additionally, we observed lower antimicrobial activity by substituting positive and aromatic residues with Ala in the alanine scanning assay, irrespective of the amino acid change, indicating that each amino acid is essential for the mechanism of action of the peptide. Therefore, we demonstrated that the (p-BthTX-I)2 analog, which is shorter and synthesized by an easier process leading to a more stable peptide, is the most antibacterial active peptide against multidrug-resistant bacteria and does not increase hemolysis activity.
Keywords: (p-BthTX-I)2; Ala scan; antimicrobial peptides; multidrug-resistant bacteria; p-BthTX-I